Dexmedetomidine maintains blood–brain barrier integrity by inhibiting Drp1-related endothelial mitochondrial dysfunction in ischemic stroke. (9th July 2021) - Zhou, Wei; Zhang, Yunchun; Jiao, Yingfu; Yin, Wen; Dong, Haiping; Xu, Saihong; Tang, Dan; Jiang, Junli; Shao, Jianlin; Wang, Zhenhong; Yu, Weifeng
Abstract: Stroke is the second leading cause of death and long-term disability worldwide, which lacks effective treatment. Perioperative stroke is associated with much higher rates of mortality and disability. The neuroprotective role of dexmedetomidine (Dex), a highly selective agonist of alpha2-adrenergic receptor, has been reported in a stroke rat model, and it was found that pretreatment of Dex before stroke could alleviate blood–brain barrier (BBB) breakdown. However, the underlying mechanisms are still unknown. As the brain endothelial cells are the main constituents of BBB and in high demand of energy, mitochondrial function of endothelial cells plays an important role in the maintenance of BBB. Given that dynamin-related protein 1 (Drp1) is a protein mediating mitochondrial fission, with mitochondrial fusion that balances mitochondrial morphology and ensures mitochondria function, the present study was designed to investigate the possible role of Drp1 in endothelial cells involved in the neuroprotective effects of Dex in ischemic stroke. Our results showed that preconditioning with Dex reduced infarction volume, alleviated brain water content and BBB damage, and improved neurological scores in middle cerebral artery occlusion rats. Meanwhile, Dex enhanced cell activity and decreased cell apoptosis in oxygen-glucose deprivation human brain microvascular endothelial cells in vitro . These protective effects of Dex were correlated with the mitochondrial morphology integrality of endothelial cells, mediated by increased phosphorylation of serine 637 in Drp1, and could be reversed by α2-adrenergic receptor antagonist Yohimbine and AMP-activated protein kinase inhibitor Compound C. These findings suggest new molecular pathways involved in the neuroprotective effects of Dex in ischemic stroke. As Dex is routinely used as a sedative drug clinically, our findings provide molecular evidence that it has perioperative neuroprotection from ischemic stroke.